APLIKASI METODE DISKUSI DAN TUGAS DALAM MENINGKATKAN HASIL BELAJAR SISWA SMPN 2 PEKALONGAN TAHUN PELAJARAN 2011/2012 - Sugianto, Endri (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
The aim of the research was to increasing of science learning echievement.Â The research was to implemented by the Classroom Action Research (CAR) in SMPN 2 Pekalongan class VIII1 academic year 2011/2012. The result of this research was the application of the discussion and assignment method, students learning achievement increase from the cycle I to cycle II by 16,12%. Based on the research the researcher suggest that the scence teachers need to apply the discussion and assignment method to increase achievement of science.Â Kata kunci : Metode Diskusi dan Tugas, Hasil Belajar Siswa